Enrollment projection for the Industrial Engineering School Nongkhaem, Bangkok, Thailand for the next five years (1979-1980 to 1983-1984) and its implications to space utilization and faculty requirements - Yamchuti, Nophawan (Animo Repository, 1979)
The purpose of this study is to study and analyze the enrollment of the Industrial Engineering School, Nongkhaem, Bangkok, Thailand for the last seven years (1972-1973-1978-1979) with the aim of projecting the school population for the next five years (1979-1980-1983-1984) and also to study and analyze the utilization of space to determine the capacity of the school as well as the assessment of future requirements of manpower. In this particular study, the data used were obtained from the enrollment figures for the past seven years, that is, from school year 1972-1973 to school year 1978-1979 of the Industrial Engineering School, Nongkhaem, Bangkok, Thailand. Three methods were used. First, the linear method used in projecting the enrollment figures for the next five years as the total population of the school as well as by department. The second method is percentage distribution, used to project the enrollment figures by departments and also as a total number. And lastly, the average rate of change of enrollment which was used to project the enrollment of the agriculture department. On the other hand, for analyzing the utilization of space for the current school year (1978-1979) of the Industrial Engineering School, Nongkhaem, Bangkok, Thailand, two methods were used. The first is the room utilization rate which was based on the number of hours used in a week. The second one is the station utilization rate which was based on the number of students who used the classroom per week. The findings based on the analysis of the data led the researcher to draw the following conclusions: 1) That there was a fluctuation of enrollment, that is a downward and upward trend of enrollment in the past seven years. One common trend that ran through all is caused by the dropping out of the first year students. 2) Among all departments, auto-mechanics department is the most popular for the last seven years electricity department is the second and the less popular, agriculture department. 3) With the present number of twenty cla